Clinicopathologic, immunophenotypic, and molecular analysis of subcutaneous panniculitis-like T-cell lymphoma: A retrospective study in a tertiary care center - Suthinee Rutnin (2020)
© 2018 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd. Background: Subcutaneous panniculitis-like T-cell lymphoma (SPTL) as strictly defined by World Health Organization-European Organization for Research and Treatment of Cancer classification is a rare cytotoxic α/β T-cell lymphoma, characterized by primary involvement of subcutaneous tissue mimicking panniculitis. Objectives: To describe the clinicopathologic, immunophenotypic, and molecular features of SPTL. Methods: A 10-year retrospective study of 18 patients diagnosed with SPTL was thoroughly reviewed according to clinicopathology, immunophenotype, and T-cell receptor (TCR) gene rearrangement. Results: Of the 18 patients, 16 patients were definitely diagnosed with SPTL. The median age was 26 years (ranged 14-53 years) with female predominance. Most patients presented with prolonged fever and subcutaneous nodules and/or plaques, usually located on lower extremities. 37.5% of patients had hemophagocytic syndrome. The main histopathology was lobular panniculitis with rimming of atypical lymphocytes highlighted by CD3+, CD8+, Beta-F1+, granzyme B+, and Ki-67 (50%-90%). Monoclonal TCR gene rearrangement was found in 50% of patients and upper extremities involvement indicated a poor prognosis. Conclusion: The correlation between clinicopathologic and immunophenotypic study is the most helpful method to give a precise diagnosis of SPTL. Rimming of CD8+ atypical lymphocytes highlighted by high Ki-67 index is highly specific for the diagnosis of SPTL.